The Mid-Infrared Instrument for the James Webb Space Telescope, VI: The Medium Resolution Spectrometer. (4th January 2016) - Wells, Martyn; Pel, J.-W.; Glasse, Alistair; Wright, G. S.; Aitink-Kroes, Gabby; Azzollini, Ruymán; Beard, Steven; Brandl, B. R.; Gallie, Angus; Geers, V. C.; Glauser, A. M.; Hastings, Peter; et al.
Abstract: We describe the design and performance of the Medium Resolution Spectrometer (MRS) for the JWST -MIRI instrument. The MRS incorporates four coaxial spectral channels in a compact opto-mechanical layout that generates spectral images over fields of view up to 7.7 × 7.7″ in extent and at spectral resolving powers ranging from 1300 to 3700. Each channel includes an all-reflective integral field unit (IFU): an "image slicer" that reformats the input field for presentation to a grating spectrometer. Two 1024 × 1024 focal plane detector arrays record the output spectral images with an instantaneous spectral coverage of approximately one third of the full wavelength range of each channel. The full 5-28.5 μm spectrum is then obtained by making three exposures using gratings and pass-band-determining filters that are selected using just two three-position mechanisms. The expected on-orbit optical performance is presented, based on testing of the MIRI Flight Model and including spectral and spatial coverage and resolution. The point spread function of the reconstructed images is shown to be diffraction limited and the optical transmission is shown to be consistent with the design expectations.